Analysis of Character Values in Fair Book and Children's Story Books - Munawaroh (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Instilling character values ​​in early childhood is very important to be carried out since children begin to grow and develop so that when children begin to know our environment as parents or educators, we can instill character education in various ways and methods that we know, such as habituation, example, storytelling or tell children about the character values ​​we want them to have. In fairy tales or children's stories there are many character values ​​that need to be owned by children. Why with fairy tales or stories? Because with fairy tales or stories, children will feel enthusiastic about listening, feel interested and happy to follow the storyline so that we can easily insert the character values ​​that we want can be absorbed by children which in the end they will naturally have these characters. The purpose of this research is to find out the extent to which character values ​​can be instilled in early childhood through fairy tales and stories. This study uses the literature review method on fairy tale books as the object of our research.